Analysis of acetaminophen, mefenamic acid, sibutramine hydrochloride, and sildenafil citrate - Eva Susanty Simaremare, Rizka Agustine Susilowati, Yeyen Dwi Astuti, Rusadi Hermawan, Elsye Gunawan, Rani Dewi Pratiwi, Rusnaeni (Journal of Applied Pharmaceutical Science, 2018)
Jamu, Indonesia herbal medicine, has long been used for helping to heal many diseases. But nowadays, many of jamu were adulterated with chemical drugs that are harmful to consumers. Adulterations were analyzed in several places except in Papua Jayapura. We conducted an analysis of jamu which containing acetaminophen (ACE), mefenamic acid (MEFA), sibutramine hydrochloride (SH), and sildenafil citrate (SILC). Samples were taken by representing herbal that predicted containing chemicals. Thin-layer chromatography and UV-Vis spectrophotometry methods were used for quantitative analysis while the determination of concentration was used by titration and UV-Vis spectrophotometry methods. In this study, we reported that there was one sample in herbal medicines containing ACE, three samples containing MEFA, two samples of slimming herbal contained SH, and three samples of aphrodisiac herbal contained SILCs.
Keywords: Acetaminophen, mefenamic acid, sibutramine hydrochloric, sildenafil citrate, Indonesia herbal medicines, Jamu.